Manajemen Mutu dan Keamanan Pangan Tuna Loin Beku di PT. Aneka Sumber Tata Bahari , Tulehu, Maluku Tengah: Quality Management and Food Safety of Frozen Tuna Loin at PT Aneka Sumber Tata Bahari, Tulehu, Central Maluku - Wagola, Ariati; Lalopua, Vonda; Apituley, Yolanda (Media Teknologi Hasil Perikanan, 2024)
Quality assurance and consumer safety protection are the main things in every processing industry. As a product with potential economic value and can even become an export commodity, frozen tuna loin should be handled carefully from catching to consuming. This research aims to analyze the process of handling tuna loin and the level of implementation of the basic feasibility of GMP (Good Manufacturing Practices) and SSOP (Standard Sanitation Operating Procedures) at PT ASTB. Based on observations, it is known that the processing of frozen tuna loin consists of 19 stages starting from Receiving Raw Materials, Weighing I, Washing I, Skinning, Trimming I, Weighing II, Washing II, Clear Smoke, Cooling, Ozone Gas Spraying, Trimming II, Weighing III, Vacuum, ABF Freezing, Metal Detector, Packaging and Labeling, Final Weighing, Frozen Storage, and Loading. Implementing the basic feasibility of GMP and SSOP has generally been carried out following the provisions; however, the company's location still needs to comply with the requirements because it is still close to residential areas and does not have separate entrance and exit access. Keywords: Frozen Tuna Loin, Quality, Export, GMP, SSOP